Bryophytes of Boryslav oil deposit and their tolerance for petroleum pollution (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
On the territory of siх working oil wells of Boryslav, species composition and ecological preferences of mosses is analysed. Morpho-physiological variability of Ceratodon purpureus and its oil pollution tolerance features is investigated experimentally.
Keywords: mosses, oil pollution, ecological groups, life forms, photosynthesis, pigments, tolerance.